Dissolved Oxygen Regulatory System Using Fuzzy Logic Method Based on Teensy Board Microcontroller - Fajar Budiman; Muhammad Rivai; Luthfi Riadhi; Devy Kuswidiastuti (JAREE (Journal on Advanced Research in Electrical Engineering), 2019)
Dissolved oxygen in water becomes a critical factor in the cultivation of fish hatcheries that determines the success/failure rate in the process of improving the quality and quantity of fish hatcheries. Low dissolved oxygen levels cause deficient to the process of decomposition, reproduction, and growth of fish. In this study, a system that can regulate the levels of dissolved oxygen in water is designed and built by utilizing the Dissolved Oxygen Meter of AZ-8403 as a sensor. The percentage of oxygen in water is controlled by Fuzzy Logic implemented in the Teensy board microcontroller. When the oxygen level is below the setting point, the aerator is then activated to produce dissolved oxygen in the water. The test results conducted on the aquarium containing fish obtained error for the reading of dissolved oxygen sensor of 0.075%. The system response requires 1 minute to reach the setting point.Keywords: dissolved oxygen, fuzzy logic control, teensy board.